Analisis Sistem Budidaya Tomat Hidroponik dalam Meningkatkan Produktivitas dan Efisiensi Sumber Daya - Alleta Aurel Kanayla; Padly Rachmat Hanansyah; Nadya Ayu Narasanti; Hafizha Novrilia Azzahra; Rifki Awaludin; Keisha Aulia Tsani Susanto Putri; Frita Zulfira; Ayesha Ayu Naura; Azzahra Putri Nathasya; Agief Julio Pratama; Ririh Sekar Mardisiwi; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2026)
Poor soil quality and inefficient nutrient utilization remain major constraints in tomato (Solanum lycopersicum L.) cultivation, often resulting in reduced plant growth, lower productivity, and suboptimal fruit quality. This study aims to evaluate the growth performance of rose tomatoes through the integration of open-field cultivation and hydroponic planting systems. The research methods included land preparation using the Pythagorean technique to ensure proper spacing and planting layout, the application of organic fertilizers to improve soil fertility, and the transition to a hydroponic drip irrigation system using rockwool as the growing medium during weeks 1 to 7 of plant development. Plant growth parameters, including plant height, leaf development, stem vigor, and overall plant health, were observed throughout the cultivation period. The results indicated that the combination of appropriate soil management practices and precise nutrient delivery in the hydroponic system significantly enhanced nutrient uptake and supported healthy plant growth. Furthermore, the drip irrigation system helped optimize water use efficiency while reducing nutrient losses. This integrated cultivation approach demonstrated its potential as an effective solution for maintaining crop quality and productivity, particularly in areas with limited land resources. Overall, the findings suggest that integrated management practices can provide a practical, efficient, and sustainable strategy for farmers seeking to improve horticultural production in modern agricultural systems.